Design Computing and Cognition '10 - Gero, John S. (Springer Netherlands : Imprint: Springer, 2011)
This volume contains the refereed and revised papers of the Fourth International Conference on Design Computing and Cognition (DCC'10), held in Stuttgart, Germany. The material in this book represents the state-of-the-art research and developments in design computing and design cognition. The papers are grouped under the following nine headings, describing both advances in theory and application and demonstrating the depth and breadth of design computing and design cognition: Design Cognition; Framework Models in Design; Design Creativity; Lines, Planes, Shape and Space in Design; Decision-Making Processes in Design; Knowledge and Learning in Design; Using Design Cognition; Collaborative/Collective Design; and Design Generation. This book is of particular interest to researchers, developers and users of advanced computation in design across all disciplines and to those who need to gain better understanding of designing.